Flexural behavior of steel-UHPC composite bridge slab under different curing conditions - Yanan Wang; Hongchen Wang; Yuan Chen (Scientific Reports)
Abstract In recent years, ultra-high-performance concrete (UHPC) has been widely used in bridge engineering owing to its high strength and toughness and excellent durability. UHPC can improve the stiffness of composite slabs and solve fatigue cracking and failure problems. However, the mechanical properties of UHPC are susceptible to curing conditions. Moreover, the bonding between steel and UHPC is affected by curing conditions owing to the large difference in their thermal expansion coefficients. Therefore, this study investigates the bending performance of steel-UHPC composite slabs under different curing conditions. Three steel-UHPC composite slab specimens were designed and fabricated under different curing conditions (28 days of standard curing, 48 h of curing at 70 °C and 90 °C), and subjected to bending tests to analyze their failure process, failure mode, load deflection response and load-strain curve. A finite element model was established to study the influence of the number of studs, thickness of the UHPC plate, and thickness of the steel plate on the flexural performance of the steel-UHPC composite slab. The results show that the failure mode of the steel-UHPC composite slabs under different curing conditions is complete flexural failure, and the failure process is divided into three primary stages: elastic stage, crack development stage, and yield stage. Compared with standard curing conditions, high-temperature curing can effectively inhibit the development of cracks and improve the ductility and flexural bearing capacity of steel-UHPC composite slabs. The ultimate bearing capacity of steel-UHPC composite slabs under the action of a positive bending moment is significantly influenced by the curing condition, whereas it is less affected by the action of a negative bending moment. The morphological patterns of the interface slip curves along the longitudinal axis of symmetry of the steel-UHPC composite slabs and the strain distribution laws along the height direction of the mid-span section are consistent under different curing conditions. The curing conditions had a significant impact on the interface slip within the shear bending section. Under all curing conditions, the flexural bearing capacities of the steel-UHPC composite slabs increase with the parameters, such as the number of shear studs, thickness of the steel plate, and thickness of the UHPC, but the degrees of influence of these parameters are different.